FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENINGKATAN VOLUME PENJUALAN SEPEDA MOTOR MEREK YAMAHA PADA PT. SURACOJAYA ABADI MOTOR DI MAKASSAR - Ibrahim Ahmad (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The main objective of this study was as follows: To view the factors that affect the volume of sales of Yamaha brand motorcycles in PT. Suracojaya Abadi Motor, as well as to determine the variable product, promotion, price and distribution which affects the volume of sales of Yamaha brand motorcycles in PT. Suracojaya Abadi Motor in Makassar. To implement these objectives, the use of qualitative analysis and quantitative analysis with multiple regression analysis, the validity and reliability as well as testing hipotesis.Dengan using the techniques of collecting data through observation, documentation and questionnaires. The research found that the factor product, price, distribution and promotion have a positive and significant effect on the increase in the volume of motorcycle sales in PT. Suracojaya Abadi Motor in Makassar.Dari four variables that affect the increased volume of motorcycle sales in PT. Suracojaya Abadi Motor in Makassar, the dominant variable is the promotion, this can be seen from the value that has been distandardized beta coefficient or the largest value of the variable lainnya.Nilai coefficient of determination (R2) of 0.536 means the entire variable X namely product, price, distribution and promotion has contributed 53.6% of the sales volume of motorcycles. The remaining portion of 46.4% is another factor not studied, such as high sales price, the Yamaha brand image as well as the services provided by the company.